2019
DOI: 10.1021/acs.jafc.9b01332
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition Shapes the Gut Microbiota and Bile Acid Profile in Association with Altered Gut-Liver FXR Signaling in Weaning Pigs

Abstract: Bile acids, synthesized in the liver and metabolized by microbiota, have emerged as important signaling molecules regulating immune responses and cell proliferation. However, the crosstalk among nutrition, microbiota, and bile acids remains unclear. Our study indicated that undernutrition in weaning piglets led to intestinal atrophy, increased colonic production, and systemic accumulation of lithocholic acid (LCA), deoxycholic acid (DCA), or their conjugated forms, which might be associated with decreased Lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 64 publications
(106 reference statements)
2
36
0
Order By: Relevance
“…The most common secondary BA, LCA and DCA, have been shown to induce cell apoptosis and increase intestinal permeability (5,6,28) and have been correlated with colorectal carcinogenesis (6,29) . Our recent study also revealed the detrimental effect of LCA and DCA on porcine enterocytes including suppression of cell proliferation, impairment of tight junction and inducement of inflammatory responses (22) . In light of the importance of gut microbiota in the production of secondary BA (11,12) , supplementation of probiotics appeared to be a promising nutritional strategy regulating secondary BA production and may thus aid in the improvement of intestinal health.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…The most common secondary BA, LCA and DCA, have been shown to induce cell apoptosis and increase intestinal permeability (5,6,28) and have been correlated with colorectal carcinogenesis (6,29) . Our recent study also revealed the detrimental effect of LCA and DCA on porcine enterocytes including suppression of cell proliferation, impairment of tight junction and inducement of inflammatory responses (22) . In light of the importance of gut microbiota in the production of secondary BA (11,12) , supplementation of probiotics appeared to be a promising nutritional strategy regulating secondary BA production and may thus aid in the improvement of intestinal health.…”
Section: Discussionmentioning
confidence: 73%
“…An incision was made on the middle abdomen of piglets, and ileum and liver tissue samples were collected and washed with sterile saline and snap-frozen in liquid N 2 . Approximately 2-cm length of duodenum, jejunum and ileum samples were fixed in 4 % paraformaldehyde and used for measurement of morphometry as we previously described in detail (22) .…”
Section: Study Design Animals and Samplingmentioning
confidence: 99%
See 3 more Smart Citations